Arthur Annesley, Margaret Cavendish, and Neo-Latin History. (22nd August 2018) - Begley, Justin
ABSTRACT: This article explores a hitherto unstudied copy of De vita […] Guilielmi ducis Novo-Castrensis (1668)—a Latin translation of The Life of William Cavendish (1667) by Margaret Cavendish (1623?–1673)—that Arthur Annesley (1614–1686), the First Earl of Anglesey, has heavily annotated. While Annesley owned the largest private library in seventeenth-century Britain, his copy of De vita is by far the most densely glossed of his identifiable books, with no fewer than sixty-one Latin and Greek annotations, not to mention numerous corrections and non-verbal markers. By studying Annesley's careful treatment of De vita, this essay makes an intervention into the burgeoning fields of reading and library history along with neo-Latin studies. I propose that Annesley filled the margins of De vita with quotations from Latin poets, scholars, philosophers, and historians—rather than his personal views—in a bid to form a politically impartial outlook on the British Civil Wars that was attuned to broader historical or even mythological trends.